2015
DOI: 10.1074/jbc.m114.592519
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Stress Hormones Regulate Cellular Iron Homeostasis by a Posttranscriptional Mechanism Mediated by Iron Regulatory Protein

Abstract: Background:The role of catecholamines in cellular iron homeostasis is not understood. Results: Epinephrine and norepinephrine up-regulate transferrin receptor-1, inhibit ferritin expression, and increase mitochondrial iron content in hepatic and skeletal muscle cells. Conclusion: Catecholamine stress hormones are novel regulators of cellular iron homeostasis. Significance: Catecholamines may act to increase cellular iron content to meet an increased demand during stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…The pcDNA3 plasmid construct containing Fpn 5′UTR was linearised and transcribed using in vitro transcription kit (Roche). Using 32 P–UTP labelled Fpn 5′UTR, RNA gel shift assays were performed following protocols as described before (Biswas et al, ; Tapryal et al, ). For the binding assays, 10 μg of cytoplasmic extracts were incubated with radiolabeled 5′UTR‐IRE probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pcDNA3 plasmid construct containing Fpn 5′UTR was linearised and transcribed using in vitro transcription kit (Roche). Using 32 P–UTP labelled Fpn 5′UTR, RNA gel shift assays were performed following protocols as described before (Biswas et al, ; Tapryal et al, ). For the binding assays, 10 μg of cytoplasmic extracts were incubated with radiolabeled 5′UTR‐IRE probe.…”
Section: Methodsmentioning
confidence: 99%
“…Cytosolic aconitase assay was performed as described previously (Das et al, 2009;Tapryal, Vivek, & Mukhopadhyay, 2015). Cytosolic extracts (50 μg) from uninfected and infected splenocytes were added to 0.2 mM cis-aconitate in 100 mM Tris-Cl, pH 7.4, 100 mM NaCl, BSA (0.02%) to perform aconitase assay as disappearence of cis-aconitate was followed at 25°C at 240 nm.…”
Section: Cytosolic Aconitase Assaymentioning
confidence: 99%
“…Catecholamines effectively cause the release of free-iron from hepatocytes and myocytes such that serum iron levels are increased rapidly. 41 Although this response is likely adaptive (ie, increasing nutrient availability during stress), the increase in background iron is then exacerbated by the iron release that is caused by tissue injury from noninfectious or infectious insult. This rapid double-hit creates iron levels that exceed the binding capacity of TF leading to increased CFI levels thereby increasing ROS.…”
Section: Catalytic Free Iron In Acute Illnessmentioning
confidence: 99%
“…94 The increased CFI environment seen in patients with trauma receiving massive blood transfusion is exacerbated because many trauma patients require catecholamine infusions (which increase serum iron) and suffer severe anemia from hemorrhage, which leads to the release of erythropoietin, which suppresses hepcidin generation thereby increasing CFI. 13,26,41,95 As a consequence, severe trauma is often exacerbated by high levels of CFI. Thus, patients with trauma requiring massive blood transfusion leading to high-levels of CFI may benefit from hepcidin-induced hypoferremia.…”
Section: Trauma and Transfusionmentioning
confidence: 99%
“…It is reported that catecholamines can also modulate ovarian steroidogenic activity in catfish, Heteropneustes fossilis (Joy et al, 2014). Catecholamines stress hormones like epinephrine and norepinephrine regulate energy homeostasis by regulating iron homeostasis in cells (Tapryal et al, 2015). Excess aldosterone is reported to result in decreased glucose uptake and oxidation in skeletal muscle in adult male rat, thus increasing the incidence of type2 diabetes (Selvaraj et al, 2013).…”
Section: Pharmacological Studies On Adrenal Glandmentioning
confidence: 99%